The Impact of COVID-19 and the Challenges of Post-COVID Rehabilitation in a Developing Country - Taslim Uddin; Hasna Raihan Rahim; Md Nuruzzaman Khandaker (Frontiers Media S.A., 2022)
The coronavirus disease 2019 (COVID-19) and its impact on human functioning are gaining increased interest. Like many other lower-income countries, the Bangladesh health and rehabilitation sector was adversely affected by COVID-19. Multiple challenges were identified for preparedness and medical rehabilitation during COVID-19 surges. Appropriate supervision of multispecialty long COVID clinics and attention to rehabilitation teamwork are important. Rehabilitation plays a key role in the management of patients with COVID-19 and can reduce the length of hospital stay and improve health outcomes. While waiting for people to be fully vaccinated; ensuring equitable access to COVID-19 vaccination, health care, and rehabilitation services among people with disabilities should be a part of the core mission during the pandemic. All levels of care including, critical, post-acute, or long covid clinic scale-up of rehabilitation services are needed. A physiatrist-led rehabilitation team approach is vital for the adaptation of rehabilitation interventions to improve the functional outcomes of persons with impairment and disability affected by COVID-19.